Ceramide increases free volume voids in DPPC membranes1. Issue 55 (17th June 2015) - Axpe, E.; García-Arribas, A. B.; Mujika, J. I.; Mérida, D.; Alonso, A.; Lopez, X.; García, J. A.; Ugalde, J. M.; Goñi, F. M.; Plazaola, F.
<x xml:space="preserve">Abstract</x> We have measured by positron annihilation lifetime spectroscopy (PALS) that ceramide increases the size of the free volume holes in DPPC lipid membranes.